"It's a whole new way of doing things": the digital divide and leisure as resistance in a time of physical distance. Issue 3 (3rd July 2021) - Lopez, Kimberly J.; Tong, Catherine; Whate, Alexandra; Boger, Jennifer
ABSTRACT: The COVID-19 pandemic continues to have a profound impact on the well-being and social connectedness of older adults. In an era of physical distancing, older adults' connections are changing. While digital leisure spaces are often described to enhance social connections, little is written about older adults and digital connectedness in a time of physical distancing. We completed 20 in-depth interviews with older Canadians (average age 77) during the initial wave (Spring 2020). This paper draws on critical tenets of Age Studies, leisure as resistance, and an understanding of the digital divide to reflect on interviews with older adults about their technology use during the COVID-19 pandemic. We reflect on technology use as resistance to ageist stereotypes, discuss facilitators of technology use as lived privilege that deepen the digital divide during COVID-19 for some, and identify opportunities for supporting older adults not presently using technology for social connection.